3-Dimensional Numerical Simulation of Nailed Slab System Settlement Behavior on Soft Soil - Abdurrahman, Ekie Aulia; Hardiyatmo, Hary Christady; Rifa'i, Ahmad (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2022)
The design of the YIA airport rail line is on soft soil with a depth of 12-16 m. The design of the rail line uses a 4 m high embankment. Reinforcement is carried out by the method of a nailed slab system. The nailed slab system consists of a monolithically connected slab and pile. This method is believed to be able to reduce the settlement that occurs in the foundation soil effectively. This study aims to determine the effect of using a nailed slab system that varies in length, distance, and arrangement. The data used are boring and laboratory tests. Effect of variations in length (8 m; 10 m; 12 m and 14 m), distance (0.8 m; 1.2 m; 1.6 m; and 2 m), and pile arrangement (uniform; V and W) on soil settlement foundation is done with the RS3 program. The results showed that each additional 2 m of pile length could reduce the total settlement by 48.63%-82.31% of the unreinforced foundation soil. The decrease in permits was fulfilled at the length of the piles of 12 m and 14 m. Pile spacing of 0.8 m, 1.2 m, 1.6 m, and 2 m reduced the total settlement by 69.47%, 68.78%, 67.22%, and 60.90%, respectively. On piles with a length of 12 m, distances of 0.8 m and 1.2 m fulfilled the allowable reduction. The use of the V arrangement gave the greatest reduction of 71.77% while the uniform arrangement was 68.78% and the W arrangement was 68.56%. The use of a nailed slab system as foundation soil reinforcement due to embankment load can reduce settlement effectively.